Disrupted alternative splicing for genes implicated in splicing and ciliogenesis causes PRPF31 retinitis pigmentosa. Issue 1 (December 2018) - Buskin, Adriana; Zhu, Lili; Chichagova, Valeria; Basu, Basudha; Mozaffari-Jovin, Sina; Dolan, David; Droop, Alastair; Collin, Joseph; Bronstein, Revital; Mehrotra, Sudeep; Farkas, Michael; Hilgen, Gerrit; et al.
Abstract Mutations in pre-mRNA processing factors (PRPFs) cause autosomal-dominant retinitis pigmentosa (RP), but it is unclear why mutations in ubiquitously expressed genes cause non-syndromic retinal disease. Here, we generate transcriptome profiles from RP11 (PRPF31 -mutated) patient-derived retinal organoids and retinal pigment epithelium (RPE), as well asPrpf31 +/− mouse tissues, which revealed that disrupted alternative splicing occurred for specific splicing programmes. Mis-splicing of genes encoding pre-mRNA splicing proteins was limited to patient-specific retinal cells andPrpf31 +/− mouse retinae and RPE. Mis-splicing of genes implicated in ciliogenesis and cellular adhesion was associated with severe RPE defects that include disrupted apical – basal polarity, reduced trans-epithelial resistance and phagocytic capacity, and decreased cilia length and incidence. Disrupted cilia morphology also occurred in patient-derived photoreceptors, associated with progressive degeneration and cellular stress. In situ gene editing of a pathogenic mutation rescued protein expression and key cellular phenotypes in RPE and photoreceptors, providing proof of concept for future therapeutic strategies. Mutations in pre-mRNA processing factors cause autosomal dominant retinitis pigmentosa. Here the authors provide insights into the pathophysiological mechanisms underlying non-syndromic retinal disease caused by heterozygous mutations in genes encoding ubiquitously expressed splicing factors.